Studi Efektivitas Transportasi Umum di Makassar - Ishak Ishak; Taufiq Natsir (Seminar Nasional LP2M UNM, 2017)
This study aims to reveal effectivity of public transport on some congestion points in Makassar and what government does in solving this problem. this research using qualitative method focusing on how and why people act, thinking, and make meaning of what they do. Data collected through interview ,questionnaire and observation. data analyzed with descriptive and qualitative. Data reduction, presentation, conclusion/verified and suggestion from experts become main concern in this study. Thera are positive and negative perspective on handling public transport, in positive way, public transport can reduce capacity of roadway in other side there are many persons do not responsible in dealing public transport and also many crime in that. Strategy of government to overcome congestion to reveal community from this situation is by making improvement of facility of public transport including road wide and highway.